2021
DOI: 10.1186/s12887-021-02938-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific associations of pregnancy-related anxiety with placental epigenetic patterning of glucocorticoid response genes and preschooler’s emotional symptoms and hyperactivity

Abstract: Backgroud We have recently reported that maternal prenatal pregnancy-related anxiety predicts preschoolers’ emotional and behavioral development in a gender-dependent manner. This study aims to test for this gender-specific effect in a different cohort and investigate whether the gender difference was specific to placental methylation of genes regulating glucocorticoids. Methods A total of 2405 mother–child pairs from the Ma’anshan Birth Cohort Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…For example, prenatal maternal depressive symptoms have been associated with lower levels of DNA methylation of NR3C2 promoter region in placenta tissue (Galbally et al, 2020). A factor score analysis yielded a sex-specific effect on DNA methylation with prenatal stress, in which the NR3C1 and HSD11B2 methylation factor scores were associated with hyperactivity and emotion symptoms only in boys (Liu et al, 2021). While our study did not address placental epigenome, we have identified several epigenetic regulators, such as key components of the Polycomb Repressive Complex 2 (PRC2) as well as molecules involved in microRNA processing, to be potential upstream regulators and mediators of the altered placental transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prenatal maternal depressive symptoms have been associated with lower levels of DNA methylation of NR3C2 promoter region in placenta tissue (Galbally et al, 2020). A factor score analysis yielded a sex-specific effect on DNA methylation with prenatal stress, in which the NR3C1 and HSD11B2 methylation factor scores were associated with hyperactivity and emotion symptoms only in boys (Liu et al, 2021). While our study did not address placental epigenome, we have identified several epigenetic regulators, such as key components of the Polycomb Repressive Complex 2 (PRC2) as well as molecules involved in microRNA processing, to be potential upstream regulators and mediators of the altered placental transcriptome.…”
Section: Discussionmentioning
confidence: 99%